Prevalence of psychosomatic and genitourinary syndrome among menopausal women: a systematic review and meta-analysis - Hussain, Nik Hazlina Nik; Noor, Norhayati Mohd; Ismail, Shaiful Bahari; Ahmad, Nik Muhammad Arif Nik (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2022)
Introduction: The menopausal transition represents the passage from reproductive to non-reproductive life and is characterized by a number of menstrual disturbances. We systematically reviewed the evidence on the prevalence of psychosomatic and genitourinary syndrome amongmenopausal women and compared the risk of symptoms between premenopausal, perimenopausal, and post-menopausal women. Methods: We performed a systematic search in MEDLINE, CINAHL, and ScienceDirect through March 2021. Case series/reports, conference papers and proceedings, articles available only in abstract form, editorial reviews, letters of communication, commentaries, systematic reviews, and qualitative studies were excluded. Two reviewers independently extracted and assessed the quality of data using the Joanna Briggs Institute Meta- Analysis. The outcomes were assessed with random-effects model using the Review Manager software. Results: In total, 29 studies had a low risk of bias and were included in the review. Our findings showed that the pooled prevalence of somatic symptoms in post-menopausal women (52.6%) was higher than in the premenopausal and perimenopausal stages (34.6 and 39.5%, respectively). There was a low prevalence of psychological symptoms in premenopausal women (28.4%). The genitourinary syndrome was highest among post- menopausal women (55.1%), followed by perimenopausal (31.9%) and premenopausal (19.2%) women. Conclusion: Post-menopausal women have a higher risk of experiencing menopausal symptoms particularly genitourinary syndrome than premenopausal and perimenopausal women. It is pertinent for healthcare professionals to evaluate the symptoms in order to provide them with a better quality of life.